2005
DOI: 10.1097/01.brs.0000175190.08134.73
|View full text |Cite
|
Sign up to set email alerts
|

Dual Growing Rod Technique for the Treatment of Progressive Early-Onset Scoliosis

Abstract: The dual growing rod technique is safe and effective. It maintains correction obtained at initial surgery while allowing spinal growth to continue. It provides adequate stability, increases the duration of treatment period, and has an acceptable rate of complication compared with previous reports using the single rod technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
349
3
22

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 569 publications
(389 citation statements)
references
References 32 publications
15
349
3
22
Order By: Relevance
“…Complications were reported also in the study performed by Akbarnia et al [10] and published in 2005. The authors revised the technique of subcutaneous rodding and used two rods instead of one and dedicated connectors for distraction procedures with routine lengthening without waiting for deformity to increase.…”
Section: Complicationssupporting
confidence: 55%
See 3 more Smart Citations
“…Complications were reported also in the study performed by Akbarnia et al [10] and published in 2005. The authors revised the technique of subcutaneous rodding and used two rods instead of one and dedicated connectors for distraction procedures with routine lengthening without waiting for deformity to increase.…”
Section: Complicationssupporting
confidence: 55%
“…While 48 % of the patients had complications of any nature, only 17 % required unplanned surgery. The authors concluded that the dual growing rod technique was safe and effective, and had an acceptable rate of complications compared with previous reports while preserving near-normal growth [10]. Consistently better results have been reported with the use of double rods instead of a single one [11,12].…”
Section: Conception and Historymentioning
confidence: 50%
See 2 more Smart Citations
“…[2,3] Convex growth arrest, combined with posterior instrumentation, has been shown to slow progression but the most reliable non-fusion surgery in infantile idiopathic scoliosis is the implantation of growing rods. [4][5][6][7] These rods control spinal curvature and guide growth, permitting a delay to fusion and hence more favourable respiratory and cosmetic outcomes.…”
Section: Introductionmentioning
confidence: 99%